Pengaruh Kepercayaan, Kemudahan Dan Kualitas Informasi Terhadap Keputusan Pembelian Secara Online Dengan Pengalaman Berbelanja Sebagai Variabel Moderasi (Studi Kasus Pelanggan Shopee Di Kecamatan Tamalanrea) - Yusril B; Baharuddin Semmaila; Imaduddin Imaduddin (Universitas Pahlawan Tuanku Tambusai, 2026)
The objective of this study is to analyze the influence of trust, ease of use, and information quality on online purchase decisions on Shopee, as well as to analyze the role of shopping experience in moderating the influence of trust, ease of use, and information quality on online purchase decisions on Shopee. This study employs a quantitative approach. The population consists of Shopee users residing in Tamalanrea District, with a sample size of 158 respondents. Data collection was conducted via questionnaires, and data analysis utilized Moderated Regression Analysis (MRA) processed using SPSS. The research results indicate that trust has a positive and significant effect on online purchasing decisions. Ease of use has a positive and significant effect on online purchasing decisions. Information quality has a positive and significant effect on online purchasing decisions. Shopping experience can moderate or strengthen the effect of trust on online purchasing decisions. Shopping experience can moderate or strengthen the effect of ease of use on online purchasing decisions. Shopping experience can moderate or strengthen the effect of information quality on online purchasing decisions. Keywords: Trust, Ease of Use, Information Quality, Purchase Decision, and Shopping Experience.